The Study of Medieval Chant: Paths and bridges, East and West - Jeffery, Peter (Cambridge Boydell & Brewer, 2001)
Gregorian chant was the dominant liturgical music of the medieval period, from the time it was adopted by Charlemagne's court in the eighth century; but for centuries afterwards it competed with other musical traditions, local repertories from the great centres of Rome, Milan, Ravenna, Benevento, Toledo, Constantinople, Jerusalem, and Kievan Rus, and comparative study of these chant traditions can tell us much about music, liturgy, literacy and culture a thousand years ago. This is the first book-length work to look at the issues in a global, comprehensive way, in the manner of the work of Kenneth Levy, the leading exponent of comparative chant studies. It covers the four most fruitful approaches for investigators: the creation and transmission of chant texts, based on the psalms and other sources, and their assemblage into liturgical books; the analysis and comparison of musical modes and scales; the uses of neumatic notation for writing down melodies, and the differences wrought by developmental changes and notational reforms over the centuries; and the use of case studies, in which the many variations in a specific text or melody are traced over time and geographical distance. The book is therefore of profound importance for historians of medieval music or religion - Western, Byzantine, or Slavonic - and for anyone interested in issues of orality and writing in the transmission of culture.PETER JEFFERY is Professor of Music History, Princeton University. Contributors: JAMES W. McKINNON, MARGOT FASSLER, MICHEL HUGLO, NICOLAS SCHIDLOVSKY, KEITH FALCONER, PETER JEFFERY, DAVID G. HUGHES, SYSSE GUDRUN ENGBERG, CHARLES M. ATKINSON, MILOS VELIMIROVIC, JORGEN RAASTED+, RUTH STEINER, DIMITRIJE STEFANOVIC, ALEJANDRO PLANCHART.
Keywords: Middle Ages (500-1400); Plainchant